Analisis Pengaruh Kebijakan Hutang, Profitabilitas, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Nurindra, Nurindra; Rinofah, Risal; Sari, Pristin Prima (Cv. Syntax Corporation Indonesia, 2024)
The purpose of the study was to determine how debt policy, profitability and managerial ownership affected the firm value.the debt policy was estimated by Debt-to-Equity Ratio (DER), profitability by Return on Equity (ROE). The time frame that was used in this study is five years, from 2018 to 2022. The traditional assumption test and multiple linear regression analysis are utilized in this quantitative study. The purposive sampling method was used to select the sample for this study, which consisted of 50 observations from 10 bussiness over the course of five years. A company’s primary objective is to increase its value. According to the findings of the study, debt policy had a negative impact on the firm value, profitability had a positive impact on the firm value, and managerial ownership had a significant negative impact on the firm value.